Właściwy Tor . biuletyn informacyjny NSZZ "Solidarność" Kolejarzy Pomorskiego OKP, no. 9, 1981 - "Solidarność", [ed. Henryk Jarząbek] (NSZZ "Solidarność" Kolejarzy Pomorskiego OKP, 1981)
Creation and circulation: For organizational use; After introduction of the Martial Law publication suspended. Republished in 1989